2004
DOI: 10.1158/0008-5472.can-03-3104
|View full text |Cite
|
Sign up to set email alerts
|

Luteolin Inhibits Vascular Endothelial Growth Factor-Induced Angiogenesis; Inhibition of Endothelial Cell Survival and Proliferation by Targeting Phosphatidylinositol 3′-Kinase Activity

Abstract: In an attempt to identify phytochemicals contributing to the welldocumented preventive effect of plant-based diets on cancer incidence and mortality, we have previously shown that certain flavonoids inhibit in vitro angiogenesis. Here, we show that the flavonoid luteolin inhibited tumor growth and angiogenesis in a murine xenograft model.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
119
1
5

Year Published

2008
2008
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 195 publications
(132 citation statements)
references
References 75 publications
(77 reference statements)
7
119
1
5
Order By: Relevance
“…Moreover, the delphinidin-induced antiproliferative effect might also be triggered by the additional contribution of an early activation of ERK1/2, overexpression of caveolin-1 and down-regulation of Ras [151]. Luteolin inhibited VEGF-induced survival and proliferation of HUVEC cells through the blockage of PI3K/AKT pathway, and the antimitotic effect of the polyphenol was mediated by inhibiting the PI3K/p70S6K pathway [152]. Similarly, apigenin also inhibited VEGF transcriptional activation through the HIF-1 binding site, decreasing HIF-1a but not HIF-1b subunit, and inhibited both AKT and p70S6K1 activation in A459 lung cancer cells [122].…”
Section: Antiangiogenesismentioning
confidence: 99%
“…Moreover, the delphinidin-induced antiproliferative effect might also be triggered by the additional contribution of an early activation of ERK1/2, overexpression of caveolin-1 and down-regulation of Ras [151]. Luteolin inhibited VEGF-induced survival and proliferation of HUVEC cells through the blockage of PI3K/AKT pathway, and the antimitotic effect of the polyphenol was mediated by inhibiting the PI3K/p70S6K pathway [152]. Similarly, apigenin also inhibited VEGF transcriptional activation through the HIF-1 binding site, decreasing HIF-1a but not HIF-1b subunit, and inhibited both AKT and p70S6K1 activation in A459 lung cancer cells [122].…”
Section: Antiangiogenesismentioning
confidence: 99%
“…The anticancer effect of Lu also is associated with inducing apoptosis, which involves redox regulation, DNA damage, and protein kinases in inhibiting the proliferation of cancer cells and suppressing metastasis and angiogenesis. 6,[10][11][12][13][14][15][16][17] Moreover, Lu has cytotoxicity in cancer cells or immortalized cells, but not in normal cells, meaning that it has fewer side effects when used in treating cancer. 8,12,18 Yet Lu has some drawbacks, such as poor water solubility (,2 × 10 −2 µmol/mL), 19 low oral absorption, 20 and bioavailability (30.4% in rats), 21 which limit its clinical application.…”
Section: Introductionmentioning
confidence: 99%
“…The phytochemical study of the extract revealed the presence of saponins, alkaloids, cardiotonic-heterosids, steroids and terpenoïds as well as tannins (Bokia, 2016). The presence of the flavonoïds could explain the antiinflammatory effect (Bagli et al, 2004;O'Leary et al, 2004), flavonoïds and alkaloïds would explain the analgesic effect (Borgi et al, 2007;Sudo et al, 2015).…”
Section: Discussionmentioning
confidence: 99%